ONLINE BOOK MANAGEMENT SYSTEM - Jose Reshma V; Kuzhanthai Theresa M; Mrs. E. Sylvia (Galaxy International Interdisciplinary Research Journal, 2022)
The project entitled “ONLINE BOOK MANAGEMENT SYSTEM” is a web application for students and teacher to Download the needed book easily. This application is developed using WordPress 7.2 and PHP as front end and My SQL 8.0 as back end. This website has two main sections BOOK and DONATE Books. The user can access the system online and search the book that theywant and can download the pdf at free of cost. In donate book selection and in order to download the pdfin book selection, the user is only allowed after filling up a form and the user can share the information. The administrator is one who maintains all the details. The uploaded pdf are published after verified by the admin.